Developing a Three Dimensional (3D) Elastoplastic Constitutive Model for Soils Based on Unified Nonlinear Strength (UNS) Criterion - Wang, Sui; Zhong, Zuliang; Chen, Bin; Liu, Xinrong; Wu, Bo (Frontiers in Earth Science, 2022)
A unified nonlinear strength criterion (UNS) is proposed, for the sake of versatility, to capture the complex strength behaviors of geomaterials under three dimensional (3D) stress paths. The UNS criterion covers wide ranges on the meridian and octahedral planes to describe nonlinear strength behaviors of soils, and which considers the effect of the intermediate principal stress on the material strength. Based on UNS strength criterion, an elastoplastic constitutive model is presented to predict the strength and deformation behavior of soils under 3D stress conditions. In addition, the proposed model, based on this unified nonlinear strength criterion, though very simple, is versatile to predict the true triaxial test results from literature when considering the influences of the intermediate principal stress on strength and deformation under complex stress conditions.